The Validity of Internships Without a Written Agreement in the MSIB Program at the Indonesian House of Representatives - Qisi Yulia Lestari; Sokhib Naim (Journal of Law Justice (JLJ), 2026)
This study aims to analyze the validity of internships conducted without a written agreement, as well as the legal consequences for students participating in the 7th Cohort of the Certified Internship and Independent Study Program (MSIB) at the House of Representatives of the Republic of Indonesia (DPR RI), based on Minister of Manpower Regulation No. 6 of 2020 concerning the Implementation of Domestic Internships. This study employs an empirical legal method with a qualitative approach, through an analysis of legislation as secondary data supplemented by primary data in the form of observations and interviews with internship participants. The novelty of this study lies in the analysis of internship practices in state institutions, which have rarely been examined from a labor law perspective, as well as in the empirical findings regarding the absence of written internship agreements in the MSIB program. The research results indicate that internships not based on a written agreement do not meet the formal requirements as stipulated in Minister of Manpower Regulation No. 6 of 2020, and thus cannot be deemed legally valid. Although there is a substantive agreement between the parties, the absence of a written document results in weak legal certainty and legal protection for interns, particularly regarding proof and the fulfillment of rights. Furthermore, pursuant to Article 10 (3) of Minister of Manpower Regulation No. 6 of 2020, such conditions have the potential to change the status of internship participants to that of employees at the relevant institution, which is clearly highly detrimental to the institution organizing the internship. This study concludes that conducting internships without a written agreement violates applicable legal provisions and results in inadequate legal protection for MSIB student participants. Therefore, organizing institutions must comply with the requirement to draft written internship agreements to ensure legal certainty and protection for internship participants.